Seed production systems hasten spread of improved varieties - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Thousands of farmers in Chad are growing improved varieties of pear) millet. The rapid adoption of new varieties is the result of an efficient seed production system. In recent years the rainfall season has been getting shorter in the region, so...